High Sensitivity C-reactive Protein (hsCRP) and its Implications in Cardiovascular Outcomes - Denegri, Andrea; Boriani, Giuseppe (Current pharmaceutical design, 2021)
Atherosclerosis and its fearsome complications represent the first cause of morbidity and mortality worldwide. Over the last two decades, several pieces of evidence have been accumulated, suggesting a central role of inflammation in atheroma development. High sensitivity C-reactive protein (hsCRP) is a well-established marker of cardiovascular (CV) disease; high levels of hsCRP have been associated with adverse CV outcome after acute coronary syndrome (ACS) and, despite some controversy, an active role for hsCRP in initiation and development of the atherosclerotic plaque has been also proposed. Randomized clinical trials focusing on hsCRP have been crucial in elucidating the anti-inflammatory effects of statin therapy. Thus, hsCRP has been progressively considered a real CV risk factor likewise to low-density lipoprotein cholesterol (LDL-C), expanding the concept of residual CV inflammatory risk. Subsequent research has been designed to investigate potential new targets of atherothrombotic protection. Despite the fact that the clinical usefulness of hsCRP is widely recognized, hsCRP may not represent the ideal target of specific anti-inflammatory therapies. Clinical investigations, therefore, have also focused on other inflammatory mediators, restricting hsCRP to an indicator rather than a therapeutic target. The aim of the present review is to provide an illustrative overview of the current knowledge of atherosclerosis and inflammation, highlighting the most representative clinical studies of lipid-lowering and antiinflammatory therapies focused on hsCRP in CV diseases.